2021
DOI: 10.1002/nop2.1110
|View full text |Cite
|
Sign up to set email alerts
|

Nursing interventions to cover patients' basic needs in the intensive care context – A systematic review

Abstract: Aim To examine the content, theoretical frameworks and effectiveness of nursing interventions utilizing patient‐reported outcome measures (PROMs) in the intensive care unit (ICU). Design A systematic review and narrative synthesis following the guidelines of the preferred reporting items for systematic reviews and meta‐analysis checklist. Methods We searched the MEDLINE, CINAHL, PsycINFO, SweMed and Cochrane controlled trials register (CENTRAL) databases for studies evaluating interventions primarily delivered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 66 publications
0
6
0
1
Order By: Relevance
“…This included providing independent nursing care, taking responsibility for the required patient care and maintaining professional behaviour. The importance of being able to provide independent nursing care has been well-documented in previous studies 40. However, a study found that critical care nurses considered a lack of professional autonomy despite having high professional responsibilities as one of the reasons for considering leaving critical care 41.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This included providing independent nursing care, taking responsibility for the required patient care and maintaining professional behaviour. The importance of being able to provide independent nursing care has been well-documented in previous studies 40. However, a study found that critical care nurses considered a lack of professional autonomy despite having high professional responsibilities as one of the reasons for considering leaving critical care 41.…”
Section: Discussionmentioning
confidence: 97%
“…The importance of being able to provide independent nursing care has been well-documented in previous studies. 40 However, a study found that critical care nurses considered a lack of professional autonomy despite having high professional responsibilities as one of the reasons for considering leaving critical care. 41 The nurse participants in our study viewed professional autonomy and being accountable to such autonomy as essential aspects of providing high-quality postresuscitation care to both patients and their families.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a regular update of SAFE to remain relevant and effective was recommended by the nurses in this study and is also supported by previous research ( Moldskred et al, 2021 ). Nurses who used a nursing documentation systems and standardized care plans in home care, reported needing regular updates to ensure that the system remained relevant to the needs of patients and the practice of nurses ( Larsen et al, 2022 ; Moldskred et al, 2021 ; Ree et al, 2019 ). Overall, the findings of this study highlight the importance of ongoing support and training, clear guidelines and routines, and regular updates to ensure the effectiveness of tools in home care.…”
Section: Discussionmentioning
confidence: 99%
“…The experience of the ICU and critical illness affects the patient in particular, but also the family members and the family as a unit [ 4 , 5 ]. The family is important for the patient’s recovery and require information to be able to cope and give the patient the best support [ 6 ]. Identifying those families putting a greater access to those in need of more follow-up/information can increase mental and physical well-being of both the patient and their family members.…”
Section: Introductionmentioning
confidence: 99%